Effectiveness of E-Services and Order of Population Administration in Jember Regency - Zulfa Mazidah; Djoko Poernomo; Ika Sisbintari (Jurnal Multidisiplin Madani, 2023)
This research examines the effectiveness of population administration services through a. The method used in this research is descriptive-qualitative. Data collection techniques in this study were carried out by means of observation, interviews, distributing and filling out questionnaires/questions, and documentation studies. This study uses a construct validity test. As for testing the validity of the data, researchers used triangulation techniques. The results of the study show that the application of the Service Information System (SIP) for the E-KTP population administration at the Jember Regency Population and Civil Registration Service is at an effective level. From each indicator, starting from achieving goals, integration, to adaptation, it shows that the application of the Service Information System (SIP) in the E-KTP population administration service at the Jember Regency Population and Civil Registration Office is running effectively. Application of the Service Information System (SIP) in realizing orderly administration at the Jember Regency Population and Civil Registration Office, especially in the management of E-KTP documents. The method used in this research is descriptive-qualitative. Data collection techniques in this study were carried out by means of observation, interviews, distributing and filling out questionnaires/questions, and documentation studies. This study uses a construct validity test. As for testing the validity of the data, researchers used triangulation techniques. The results of the study show that the application of the Service Information System (SIP) for the E-KTP population administration at the Jember Regency Population and Civil Registration Service is at an effective level. From each indicator, starting from achieving goals, integration, to adaptation, it shows that the application of the Service Information System (SIP) in the E-KTP population administration service at the Jember Regency Population and Civil Registration Service is running effectively